Organoid intelligence (OI): the new frontier in biocomputing and intelligence-in-a-dish - Smirnova, Lena; Caffo, Brian S.; Gracias, David H.; Huang, Qi; Morales Pantoja, Itzy E.; Tang, Bohao; Zack, Donald J.; Berlinicke, Cynthia A.; Boyd, J. Lomax; Harris, Timothy D.; Johnson, Erik C.; Kagan, Brett J.; et al. (Frontiers in Science, 2023)
Biological computing (or biocomputing) offers potential advantages over silicon-based computing in terms of faster decision-making, continuous learning during tasks, and greater energy and data efficiency. We present a vision and collaborative program for the multidisciplinary scientific and engineering field of ‘organoid intelligence’ (OI), which aims to ethically employ scientific and bioengineering advances to harness human stem-cell-derived brain organoids for biocomputing purposes. Our model is based on standardized, high-density, three-dimensional, myelinated brain organoids enriched with cells and genes critical for learning. Integrated microfluidic systems can support scalable and durable culturing together with spatiotemporal chemical signaling, while innovative microelectrode arrays and probes permit high-resolution spatiotemporal electrophysiological signaling inputs and recording outputs. We envisage complex networks that interface brain organoids with sensors and output devices, and which ultimately interface multiple brain and sensory organ organoids (e.g. retinal organoids). Training these systems requires novel biofeedback, big data warehousing, and machine learning methods. An embedded ethics approach will be used to identify and analyze the ethical aspects raised by OI research in an iterative, collaborative manner involving all relevant stakeholders. The many possible applications of this research urge the strategic development of OI as a scientific discipline. For example, in addition to biocomputing, the development of “intelligence-in-a-dish” also offers unparalleled opportunities to elucidate the biological basis of human cognition, learning and memory, and the pathophysiology of developmental and degenerative diseases (such as Alzheimer’s disease and other forms of dementia) – potentially aiding innovative approaches to treatment or prevention in fields of global unmet need.